Assessment of the construction of social knowledge. - Saldarriaga Vélez, Óscar (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This article presents a semantic analysis of systems of meaning in students of 5th and 9th gradesin Bogotá schools. The present project analyzes student commentaries based on a quote takenfrom the national curriculum guidelines in social sciences. This analysis is grounded on thetheories of Greimas and Hiernaux.